2008
DOI: 10.1152/japplphysiol.01091.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β and myostatin signaling in skeletal muscle

Abstract: Kollias HD, McDermott JC. Transforming growth factor-␤ and myostatin signaling in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
238
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(254 citation statements)
references
References 83 publications
8
238
3
5
Order By: Relevance
“…The type I receptor is the center of the signaling as it is essential for signal specificity as well as for signal propagation beyond the plasma membrane. 15,16 Cross-linking studies demonstrated that activin receptor IIB (ACVR2B) is the primary type II receptor for myostatin. 37,38 Blocking the activity of this receptor in mice models leads to dramatic increases in muscle mass, comparable with those seen in myostatin knock out mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type I receptor is the center of the signaling as it is essential for signal specificity as well as for signal propagation beyond the plasma membrane. 15,16 Cross-linking studies demonstrated that activin receptor IIB (ACVR2B) is the primary type II receptor for myostatin. 37,38 Blocking the activity of this receptor in mice models leads to dramatic increases in muscle mass, comparable with those seen in myostatin knock out mice.…”
Section: Discussionmentioning
confidence: 99%
“…ACVR1B got the highest ranking because of its high significance in both the combined linkage and association approach (Figure 2) and the familybased association analyses (Figure 3), and because the ACVR1B protein has a role in the molecular TGFb pathway regulating the signaling of myostatin, a negative regulator of skeletal muscle mass. 15,16 Even though it ranked lower, INHBC was also included for follow-up because it is a part of the same superfamily of proteins as ACVR1B.…”
Section: Fine Mapping Stagementioning
confidence: 99%
See 1 more Smart Citation
“…As extrinsic factors, myostatin (Mstn), a member of the TGF- superfamily, has been proposed as a regulator of embryonic myogenesis [30,32,34,163,164,165,166]. Myostatin, also called GDF8 (growth differentiation factor 8), is a secreted growth factor that belongs to the transforming growth factor- (TGF-) superfamily of growth and differentiation factors [30].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Myostatin, also called GDF8 (growth differentiation factor 8), is a secreted growth factor that belongs to the transforming growth factor- (TGF-) superfamily of growth and differentiation factors [30]. In mice, myostatin is predominantly expressed in skeletal muscle tissues from the period of embryogenesis to adulthood suggesting a role for this factor in the control of muscle development and function [30,166]. The role of myostatin in muscle comes from the phenotype of myostatin-deficient animals.…”
Section: Extrinsic Pathwaymentioning
confidence: 99%